A Preliminary Study on Investigation of Blood–Brain Barrier Damage Markers in Patients with Alcohol Use Disorder Before and After Therapy. (22nd August 2022) - Cetin, Ihsan; Yazla, Ece; Akmese, Bediha; Kayadibi, Hüseyin
Abstract: Aim: The use of alcohol affects the central nervous system and plays important roles in various neurological disorders through neurotoxicity resulting from blood–brain barrier (BBB) permeability. The BBB is regulated by tight junction proteins interacting closely with endothelial cells. This study evaluated the serum levels of proteins and spectrin degradation products associated with BBB damage in patients with alcohol use disorder. Methods: This preliminary case–control study was conducted with 30 healthy volunteers and 26 alcohol use disorder patients. The serum levels of spectrin breakdown product 145 (SBDP145), spectrin breakdown product 150 (SBDP150), ubiquitin carboxy-terminal hydrolase L1 (UCHL1), ubiquitin ligase cullin-3 (ULC), occludin and claudin were measured with enzyme-linked immunosorbent assay. Results: There was no significant difference between the levels of SBDP145, SBDP150, UCHL1, ULC, occludin and claudin before and after treatment in patients with alcohol use disorder. SBDP150 levels were significantly lower in patients than controls ( P  < 0.001). The area under the curve was 0.841 (0.733–0.949) with the 95% confidence interval for SPDP150. Conclusion: A decrease of the serum SBDP150 levels appears to be associated with alcohol use disorder. Future studies might clarify whether diminished serum SBDP150 levels are associated with BBB damage in patients with alcohol use disorder.